Feasibility, reliability, and clinical value of genomic assay on pre-therapeutic biopsy for endocrine receptor-positive HER2-negative early breast cancer - Gilles Houvenaeghel; Maxime Souquet Bressand; Valérie Juhan Duguet; Monique Cohen; Catherine Bouteille; Laura Sabiani; Julien Barrou; Loic Juquel; Véronique Brunel; Olivia Quilichini (Frontiers in Oncology, 2026)
Endocrine receptor-positive (ER+) and HER2-negative breast cancer (BC) represents approximately 80% of all BCs. Most patients are treated with upfront surgery; however, 15%–30% will develop late recurrences. Genomic assay indication is usually based on postoperative pathological data including histology subtype, tumor size, lymph node status, SBR grade, and Ki67. Performing genomic testing on core needle biopsy specimens prior to surgery may offer several advantages. In this manuscript, we assess the feasibility, reliability, utility, and potential benefits of such genomic analyses performed on core needle biopsies. Several factors may lead to proposing genomic assay analysis on biopsy: (1) optimization of the patient pathway by reducing time to therapeutic decision-making, (2) predicting response to neoadjuvant chemotherapy (NAC) or neoadjuvant endocrine therapy (NET), and (3) refining prognostic assessment to guide adjuvant chemotherapy decisions in patients for whom axillary surgery is not planned. Given the feasibility and reliability of genomic assay on core needle biopsies, it can be suggested that this practice may become more common in the near future. Knowledge of the evolutive risk determined by the result of genomic assay, as well as clinicopathological characteristics, allows more precise personalization of the therapeutic strategy, including the choice between upfront surgery and neoadjuvant therapy, the selection of systemic treatments, and decision-making in the absence of axillary staging.